Slit2 as a β-catenin/Ctnnb1-dependent retrograde signal for presynaptic differentiation - Wu, Haitao (eLife, 2015)
Neuromuscular junction formation requires proper interaction between motoneurons and muscle cells. β-Catenin (Ctnnb1) in muscle is critical for motoneuron differentiation; however, little is known about the relevant retrograde signal. In this paper, we dissected which functions of muscle Ctnnb1 are critical by an in vivo transgenic approach. We show that Ctnnb1 mutant without the transactivation domain was unable to rescue presynaptic deficits of Ctnnb1 mutation, indicating the involvement of transcription regulation. On the other hand, the cell-adhesion function of Ctnnb1 is dispensable. We screened for proteins that may serve as a Ctnnb1-directed retrograde factor and identified Slit2. Transgenic expression of Slit2 specifically in the muscle was able to diminish presynaptic deficits by Ctnnb1 mutation in mice. Slit2 immobilized on beads was able to induce synaptophysin puncta in axons of spinal cord explants. Together, these observations suggest that Slit2 serves as a factor utilized by muscle Ctnnb1 to direct presynaptic differentiation. DOI: http://dx.doi.org/10.7554/eLife.07266.001